Correlation Of Albumin Levels With Glucose Levels in Hypoglycemic Patients After The Use Of Insulin Therapy - Fajari, Nanang Miftah; Kholifah, Rika; Rosida, Azma (Clinical and Research Journal in Internal Medicine, 2024)
Background: Most of the incidence of hypoglycemia in hospital (11.29%) is caused by administering insulin therapy as a therapeutic modality in diabetes mellitus patients during hospitalization. The bond between albumin and insulin using the help of fatty acids makes insulin control the body's glycemic levels. Aim: The purpose of this study was to determine and analyze the correlation between albumin levels and glucose levels in hypoglycemia patients after the administration of insulin therapy at the Ratu Zalecha General Hospital. Methods: This study was an analytic observational study with a cross-sectional approach. A total of 32 samples were obtained by purposive sampling Results: The patient's mean glucose level was 48.95 ± 11.5 mg/dL and the patient's mean albumin level was 2.4 ± 0.6 g/dL. Bivariate analysis using Pearson's correlation test showed a correlation between albumin levels and glucose levels (p = 0.045 <0.05; r = 0.356). Conclusion: The conclusion is that there is a significant correlation between albumin levels and blood glucose levels, the direction of the positive correlation with the strength of the weak correlation in the endocrine internal medicine ward of the Ratu Zalecha Martapura Hospital.